2001
DOI: 10.1016/s0029-7844(01)01346-1
|View full text |Cite
|
Sign up to set email alerts
|

Uterosacral ligament: description of anatomic relationships to optimize surgical safety

Abstract: Our findings suggest that the optimal site for fixation is the intermediate portion of the uterosacral ligament, 1 cm posterior to its most anterior palpable margin, with the ligament on tension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 12 publications
1
69
0
8
Order By: Relevance
“…It is important to recall that routine dissection and repair of the ureters, a procedure to prevent injuries cited by some authors, increases the risks of injury of the ureter and should not be routinely done. 10 …”
Section: Anatomymentioning
confidence: 99%
“…It is important to recall that routine dissection and repair of the ureters, a procedure to prevent injuries cited by some authors, increases the risks of injury of the ureter and should not be routinely done. 10 …”
Section: Anatomymentioning
confidence: 99%
“…2 For descriptive purposes, Buller et al 23 divided the uterosacral ligaments into three equal segments: the cervical, intermediate and sacral portions, the mean widths of which were 2.0 Ϯ 0.5 cm, 2.7 Ϯ 1.0 cm and 5.2 Ϯ 0.9 cm, respectively.They also demonstrated that the ischial spine was found beneath the intermediate portion of the ligament consistently. They support the cephalic 2-3 cm of the vagina, 'level I'.…”
Section: Surgical Optionsmentioning
confidence: 99%
“…Ross 7 emphasised the importance of good apical vault support; however, paravaginal repair may be required 3,5,6 to address the complex vaginal prolapse that represents 67% of post-hysterectomy prolapse. 23 …”
Section: Sacrospinous Fixation or Uterosacral Suspensionmentioning
confidence: 99%
“…Han-Young Park, et al Effi cacy and safety of uterosacral vaginal vault suspension for pelvic organ prolapse 분은 17 kg 무게까지 지탱할 수 있어 질첨부 또는 질원개를 고정할 수 있는 튼튼한 구조물이 된다 [9]. 자궁천골인대는 요관과 밀접하게 가까 이 위치하고 있어 자궁천골인대에 봉합사를 넣을 때에 요관손상의 위험 도가 높다.…”
unclassified
“…자궁천골인대는 요관과 밀접하게 가까 이 위치하고 있어 자궁천골인대에 봉합사를 넣을 때에 요관손상의 위험 도가 높다. 요관은 자궁천골인대의 중간부분에 위치하고 있는 좌골극과 4.9 ± 2.0 cm 떨어져 있는 것으로 보고되고 있다 [9]. 그러므로 자궁천골 인대에 가장 튼튼한 봉합사를 넣기 위해서는 좌골극으로부터 내방 후방 으로 위치하게끔 중간부분을 선택하여야 한다.…”
unclassified